Elderly, Duration of Hospitalization and Hospital Cost in Milad Hospital in Iran - Mohammad Hossein Soltani; Robab Sahaf; Farahnaz Mohammadi Shahbolaghi; Shahram Ghaffari; Ardeshir Khosravi; Mahmoud Reza Gohari (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: There are much more studies about adolescence in most countries in compare with other age groups. The goal of this study is evaluation of relationship between duration of hospitalization in elderly patients in comparison to the middle ages. Methods & Materials: This is a descriptive analysis, cross sectional, case study and retrospective research that was done after gathering the data of elderly and middle age patient in MILAD Hospital. First of all prevalent causes of admission in hospital has been detected. Descriptive analysis about tow important factors include: Duration of hospitalization and bed cost has been done. By statistical tests (T.Test, Analysis Of Variance-ANOVA- and other analytical test) the results had been analyzed and compared with similar researches. Results: In this study data of 12.989 patient has been analyzed (7,279 adolescent people with age range of 60±8.73 and 5,710 middle age people with age range of 45±4.17 which 6,430 were female and 6,559 were male). Based on this study the duration of hospitalization and bed costs of adolescents has been significantly more than middle age patients (P<0.001). As well, the bed costs of people between 60-75 years old has been significantly much more than other adolescents (P<0.001). Analysis showed that bed costs and duration of hospitalization has been significantly more in men than women (P<0.001). Conclusion: 1) Elderliness increases the duration of hospitalization, 2) The longest duration of hospitalization has been for 60-75 years old patients, 3) Duration of hospitalization was longer for men than women.